On the complexity of the Escape Problem for linear dynamical systems over compact semialgebraic sets - D'Costa, J; Lefaucheux, E; Neumann, E; Ouaknine, J; Worrell, J (Schloss Dagstuhl - Leibniz-Zentrum für Informatik, 2021)
We study the computational complexity of the Escape Problem for discrete-time linear dynamical systems over compact semialgebraic sets, or equivalently the Termination Problem for affine loops with compact semialgebraic guard sets. Consider the fragment of the theory of the reals consisting of negation-free ∃ ∀-sentences without strict inequalities. We derive several equivalent characterisations of the associated complexity class which demonstrate its robustness and illustrate its expressive power. We show that the Compact Escape Problem is complete for this class.